2014
DOI: 10.1007/s10620-014-3264-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Metal Stenting with Radiofrequency Ablation Versus Stenting Alone for Treating Malignant Biliary Strictures: Is There an Added Benefit?

Abstract: RFA appears to improve survival in patients with end-stage cholangiocarcinoma and pancreatic cancer. In a disease with limited treatment options, this modality may prove to be beneficial compared to stenting alone. Randomized controlled trials and evaluation of quality of life measures should be performed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 15 publications
1
115
0
2
Order By: Relevance
“…The addition of RFA could prove beneficial to such patients, as a recent retrospective study comparing metal stenting with and without RFA showed (8). The study demonstrated that RFA was an independent predictor of survival in the treatment of malignant biliary strictures.…”
Section: A B C D F E Discussionmentioning
confidence: 92%
“…The addition of RFA could prove beneficial to such patients, as a recent retrospective study comparing metal stenting with and without RFA showed (8). The study demonstrated that RFA was an independent predictor of survival in the treatment of malignant biliary strictures.…”
Section: A B C D F E Discussionmentioning
confidence: 92%
“…Randomised studies comparing photodynamic therapy combined with biliary stenting to stenting alone have been inconsistent in showing a benefit in terms of patient survival and stent patency 37–39. Retrospective series of patients with inoperable malignant strictures have reported superior patient survival in those who had undergone radiofrequency ablation and stent placement compared with stenting alone;40 41 the results of ongoing randomised trials are keenly awaited.…”
Section: Endoscopic Therapymentioning
confidence: 99%
“…20 RFA achieves localized tumor necrosis via thermal energy and can be performed through an endobiliary and percutaneous intraductal technique. The RFA catheter (Habib Endo HPB; EMcision Ltd, London, UK) is a single-use, bipolar device used for endoluminal delivery of RFA into the biliary tree over a 0.035-inch guide wire.…”
Section: Technique/proceduresmentioning
confidence: 99%